The Role of Levan Produced from Pseudomonas fluorescens as Antipathogenic Substances and Phagocytic Enhancer against Some of Bacterial Isolates - Alaa Raheem Kazim (Journal of Global Pharma Technology, 2016)
Levan is a natural substance that produced from many organisms, levan recognized as a homopolysaccharide with multi-functional features and a wide range of potential industrial applications. Pseudomonas fluorescens had the capacity to produce levan in the total absence of air which exhibited broad antibacterial spectra against foodborne pathogenic bacteria. The results showed that three isolates of bacterial isolates were classified as a member of Pseudomonas fluorescens with antibacterial activity when tested against various pathogenic bacteria; levan has antibacterial activity against Staphylococcus. aureus, E.coli and Listeria but it had no activity against Salmonella typhi, the results showed that levan increased phagocytic activity, The phagocytic index against S.aureus increased in the presence of levan in compared with control (without levan). The phagocytic index was (65%) when used levan in concentration (200µg ∕ ml|) while the phagocytic index was (40%) in control (without levan).Keywords: Levan, Antimicrobial activity, FT-IR, Pathogenic bacteria, Phagocytic index.